Bacterial Lipoproteins Induce BAFF Production via TLR2/MyD88/JNK Signaling Pathways in Dendritic Cells - Im, Jintaek; Baik, Jung Eun; Lee, Dongwook; Park, Ok-Jin; Park, Dong Hyun; Yun, Cheol-Heui; Han, Seung Hyun (Frontiers in Immunology, 2020)
B-cell activating factor (BAFF) plays a crucial role in survival, differentiation, and antibody secretion of B cells. Microbial products with B-cell mitogenic properties can indirectly promote expansion and activation of B cells by stimulating accessory cells, such as dendritic cells (DCs), to induce BAFF. Although bacterial lipoproteins are potent B-cell mitogen like lipopolysaccharides (LPS), it is uncertain whether they can stimulate DCs to induce BAFF expression. Here, we evaluated the effect of bacterial lipoproteins on BAFF expression in mouse bone marrow–derived DCs. Lipoprotein-deficient Staphylococcus aureus mutant induced relatively low expression level of membrane-bound BAFF (mBAFF) and the mRNA compared with its wild-type strain, implying that bacterial lipoproteins can positively regulate BAFF induction. The synthetic lipopeptides Pam2CSK4 and Pam3CSK4, which mimic bacterial lipoproteins, dose-dependently induced BAFF expression, and their BAFF-inducing capacities were comparable to those of LPS in DCs. Induction of BAFF by the lipopeptide was higher than the induction by other microbe-associated molecular patterns, including peptidoglycan, flagellin, zymosan, lipoteichoic acid, and poly(I:C). Pam3CSK4 induced both mBAFF and soluble BAFF expression in a dose- and time-dependent manner. BAFF expression by Pam3CSK4 was completely absent in DCs from TLR2- or MyD88-deficient mice. Among various MAP kinase inhibitors, only JNK inhibitors blocked Pam3CSK4-induced BAFF mRNA expression, while inhibitors blocking ERK or p38 kinase had no such effect. Furthermore, Pam3CSK4 increased the DNA-binding activities of NF-κB and Sp1, but not that of C/EBP. Pam3CSK4-induced BAFF promoter activity via TLR2/1 was blocked by NF-κB and Sp1 inhibitors. Collectively, these results suggest that bacterial lipoproteins induce expression of BAFF through TLR2/MyD88/JNK signaling pathways leading to NF-κB and Sp1 activation in DCs, and BAFF-derived from bacterial lipoprotein-stimulated DCs induces B-cell proliferation.